S-Equol, a Major Isoflavone from Soybean, Inhibits Nitric Oxide Production in Lipopolysaccharide-Stimulated Rat Astrocytes Partially via the GPR30-Mediated Pathway - Mitsuaki Moriyama; Ayano Hashimoto; Hideyo Satoh; Kenji Kawabe; Mizue Ogawa; Katsura Takano; Yoichi Nakamura (International Journal of Inflammation)
Cumulative evidence indicates that estrogen receptor (ER) agonists attenuate neuroinflammation. Equol, a major isoflavone from soybean, exhibits estrogen-like biological activity, but their effect on inflammatory response has not been well established. Here, we investigated the effect of S-equol on nitric oxide (NO) production, well-known inflammatory change in astrocytes stimulated by LPS. S-Equol attenuated LPS-induced NO production with a concomitant decrease in expression of inducible NO synthase (iNOS). S-Equol did not affect LPS-induced increase in intracellular ROS production. Intracellular ER blocker ICI 182.780 had no effect on S-equol-induced decrease in NO production. Addition of G-15, antagonist of G protein-coupled receptor 30 which is nongenomic ER and located on cell surface, partially recovered S-equol-induced attenuation of NO production. These findings suggest that attenuation of NO production by S-equol may mitigate LPS-induced neuroinflammation in astrocytes. S-Equol may exert a glioprotective effect, at least in part, via a nongenomic effect.